A qualitative evaluation of a pilot leadership programme for dentists. Issue 3 (6th July 2015) - Walsh, Jonathan; Taylor, Nicholas; Hough, Donna; Brocklehurst, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper was to evaluate a pilot training programme run by Health Education North West to promote clinical leadership amongst general dental practitioners (GDPs). New powers and responsibilities for clinicians have caused a fundamental shift in the way that local services are planned and delivered in England. GDPs are being appointed onto the boards of local professional networks (LPNs) to influence the way that services are delivered at a local level. Analogous to clinical commissioning groups in medicine, the role of LPNs is to ensure that GDPs lead change and drive up the quality of service provision. Clinical leadership has been argued to be fundamentally important in these new structures, but has received little attention in the dental literature. Design/methodology/approach – Semi-structured interviews and a focus group were held with participants of the pilot to explore their understanding and experience of clinical leadership. These were recorded, transcribed verbatim and underwent thematic analysis. Findings – Nineteen codes were identified and organized into four themes: nature of clinical leadership, challenges for clinical leaders in dentistry, Leadership Exploration and Discovery programme evaluation and future direction. Practical implications – The research provides an understanding of how GDPs conceptualise clinical leadership and provides recommendations for future leadership training programmes. Originality/value – This is the first evaluation of a leadership programme for GDPs and so helps address the paucity of evidence in the dental literature.